Kontribusi Tingkat Pendidikan, Motivasi Dan Aktivitas Kegiatan Kkg Terhadap Kinerja Guru Sekolah Dasar Di Kecamatan Purwodadi - Dewi, Dyah Septiani Maha; , Dr.Suyatmini,SE.,M.Si; , Dr. Sabar Narimo,MM,M.Pd (2017)
The objectives of the study are to know the contribution of education, motivation, and KKG activity on the primary school teachers elementary school Dabin I until Dabin VIII district of Purwodadi. The research is a quantitative research. The experiment was conducted in elementary school Dabin I until Dabin VIII Purwodadi in August-November 2016. The sampleof 257 teachers. The samples in this research using random sampling techniques. The results showed that: 1) Level of Education (X1) shows that the level of education has not contributed to the performance of elementary school teachers Dabin Dabin I to VIII in the District of Purwodadi indicated by the regression coefficient - 0.338. These results reinforced the t value at -0294 while t table of 1971 or -0294 <1,971 and the value of significance for 0769> 0.05. 2) Motivation of teachers has not contributed to the performance of elementary school teachers Dabin Dabin I to VIII in the District of Purwodadi. teacher work motivation (X2) with regression coefficient of - 0.170. These results reinforced the value of the variable t teacher work motivation (X2) at -4102 while t table of 1971 or -4102 <1,971 with significance of 0.000 <0.05. 3) Activities KKG contributes to the performance of elementary school teachers Dabin Dabin I to VIII in the District of Purwodadi significantly. Unknown value regression coefficient of 0.248. These results supported the t value variable Activities Activities KKG (X3) amounted to 4,677 while t table amounted to 1,971 or 4,677 <1,971. with significance of 0.000 <0.05. 4) Contributions simultaneous levels of education, motivation and activity KKG on the performance of elementary school teachers Dabin Dabin I to VIII shown Purwodadi Subdistrict calculated F value of 10.558 while the value of F table of 2.64 or 10.558> 2.64.